2003
DOI: 10.1002/ps.694
|View full text |Cite
|
Sign up to set email alerts
|

Local early induced resistance of plants as the first line of defence against bacteria

Abstract: This paper is an overview of a non-specific local early induced resistance (EIR) mechanism, distinct from the incompatible-specific hypersensitive reaction (HR). We have shown that the local induced resistance (LIR) described earlier is not a single and uniform response to pathogen infection, because an early (EIR) and a late form can be distinguished. EIR operates from 3-6 h post-inoculation (hpi) until about 20 hpi, and is inhibited by a short heat-shock or the eukaryotic protein synthesis inhibitor, cyclohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…This a reasonably quick response relative to the 12 to 24 h generally required for production of an HR. However, PTI-induced inhibition of the HR appears to require de novo transcription and translation as it was previously reported that the protein synthesis inhibitor cycloheximide restores the HR (Klement et al, 2003). Interestingly, HR inhibition induced by flg21 lasted through 2 d, while HR inhibition induced by intact bacteria persisted over a 2-week period.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…This a reasonably quick response relative to the 12 to 24 h generally required for production of an HR. However, PTI-induced inhibition of the HR appears to require de novo transcription and translation as it was previously reported that the protein synthesis inhibitor cycloheximide restores the HR (Klement et al, 2003). Interestingly, HR inhibition induced by flg21 lasted through 2 d, while HR inhibition induced by intact bacteria persisted over a 2-week period.…”
Section: Discussionmentioning
confidence: 70%
“…The PTI-induced inhibition of the HR has previously only been reported in the solanaceous plants tobacco, N. benthamiana, and pepper (Capsicum annuum; Newman et al, 2000;Klement et al, 2003;Oh and Collmer, 2005). PTI-induced inhibition of the HR can also be recapitulated in Arabidopsis leaves (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In addition to the HR, there is a more general plant defense response that also recognizes saprophytic bacteria and bacteria without functional TTSS and subsequently inhibits their multiplication (Klement et al , 2003. There are many synonyms in the literature for this general recognition and defense system, such as basic, basal, general resistance.…”
Section: Introductionmentioning
confidence: 99%